Making meaning of reality television celebrities: the reception of South African Idol by young adults in Joza, Grahamstown - Magade, Mncedi Eddie (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
Reality television or "factual entertainment" is a hybrid of old television formats and factual programming in order to create a "new" entertaining show designed to draw the attention of audiences and increase viewership ratings. South African Idol is one popular local example. Adapted from the British programme Pop Idol, the show promises upward mobility for the young star who wins the competition. This show has become a subject of conversation amongst young people in South Africa who aspire to the "success" and "celebrity" status that is produced by participating on the show. This paper uses a Cultural Studies framework in order to examine the relationship between texts and audiences as an aspect of the "circuit of culture," with its interrelated moments of production, texts, consumption and lived experience. My research focuses on the text and audience "moments" of this circuit. Audience studies research suggests that we should situate television viewing and the meanings made of TV programs in the natural setting of the home, and that this setting should be taken seriously as a unit of analysis. This study therefore, seeks to understand the ways in which audiences make meaning of this television programme within the domestic context.
Keywords: Talent shows (Television programs) -- South Africa; Television viewers -- South Africa; Television programs -- South Africa; Mass media -- South Africa; South African Idol (Television program); Reality television shows